Clinical application of standardization right thoracic incision for thoracoscopic thymic tumor resection - Shihao Xu; Dongzhao Gao; Xinming Li; Jiagang Zhang; Jian Yang; Enji Yang; Yong Ma; Jun Qian (Journal of Cardiothoracic Surgery)
Abstract Background With the continuous development of minimally invasive thoracic surgery, thoracoscopic thymectomy has become a routine operation. This method, now widely recognized, better protects lung function, reduces intraoperative blood loss and pain, and shortens postoperative hospital stay. We now introduce a standardized right thoracic incision for thoracoscopic thymic tumor resection, which has achieved favorable clinical outcomes. Methods This retrospective study involves 63 patients who underwent standardized right thoracic incision for thoracoscopic thymic tumor resection from October 2022 to January 2024. We analyzed the relevant clinical data, including postoperative pathological diagnosis, operation time, intraoperative blood loss, chest tube drainage duration, postoperative hospital stay, and follow-up data. Results All 63 patients underwent thoracoscopic surgery. Thoracoscopic surgery excised thymic tumors and mediastinal fat in 62 cases, while 1 case of thymic carcinoma underwent thoracoscopic biopsy due to invasion of the superior vena cava and innominate vein. Postoperative pathological diagnosis revealed thymoma in 35 cases (33 cases of thymoma and 2 cases of thymic adenocarcinoma). R0 resection was achieved in 33 cases and R1 resection in 1 case. Additionally, 2 patients diagnosed with thymic adenocarcinoma were advised to undergo postoperative radiotherapy. Postoperative pathological diagnosis of the other 28 cases showed thymus hyperplasia in 13 cases and thymus cysts in 15 cases. The mean operation time was 57.3 ± 14.2 min, and intraoperative blood loss was 22.5 ± 14.7 ml. The mean chest tube drainage duration was 2.7 ± 1.3 days, and the postoperative hospital stay was 3.7 ± 1.4 days. No secondary operations were required, and no severe complications or mortality were observed during the perioperative period. All patients were discharged smoothly after surgery. Ten patients were not followed up due to recent surgery. The remaining 53 patients were followed up for 6 to 12 months, with no recurrence or distant metastasis observed. Conclusion The standardized right thoracic incision for thoracoscopic thymic tumor resection simplifies the procedure of thymectomy. The operation’s risk points are relatively fixed, making it safe and feasible. It is easy for the operator to master, and the thymic tumor resection rate is high. It possesses characteristics of being minimally invasive, enabling rapid recovery, having fewer complications, and requiring simple perioperative management.